AHL DALAM AL-QUR'AN PERSPEKTIF SEMANTIK 'AISYAH BINTU SYATHI' - Rosyid, Muhammad; Idris, Muhammad Anwar (UIN Raden Mas Said Surakarta, 2020)
Â ArabicÂ usually useÂ the wordÂ al-usrahorÂ al-â€˜ailahto refer to family.Â However, the Qurâ€™an also employs some different words to describe family, namelyÂ ahl, â€˜asyirah,Â rahtu,alu,Â qurbaandÂ ruknu.Â This article aims to examine the wordÂ ahl. This is based on the fact thatÂ ahlisÂ the most frequent wordÂ mentioned theQurâ€™an to refer to the family. Using the semantic analysisÂ proposed byÂ â€˜Aisya bint al-Syatiâ€™, this article shows that the original meaning of the wordÂ ahlisÂ â€œentitledâ€andÂ â€œappropriateâ€.Itscontextual meaning, however,might refer toÂ the people of the book (ahl al-Kitab), residents (al-sakin), followers (qawm al-NabÄ«), people who are entitled orÂ reserve the right(al-mustahaq), theÂ coreÂ family (usrah), and clans or extended family (â€˜ailah). This article contributes toÂ the ideal ofÂ building aÂ family. By referring to the meaning ofÂ ahl,the familyÂ should be correctly and appropriately built so as to achieveÂ happiness.